Analysis of Preeclampsia Risk Factors at Dr. R. Sosodoro Djatikoesoemo Bojonegoro Regency Hospital, Indonesia - Ari Tri Rahayu; Lilik Triyawati; Sri Wahyuni (Health Dynamics, 2025)
Background: Hypertension in pregnancy affects 10% of pregnant women worldwide and includes preeclampsia, eclampsia, gestational hypertension, and chronic hypertension. Preeclampsia is the most common, with a global incidence of 2–8% of pregnancies. In Indonesia, preeclampsia accounts for 128,273 cases annually, or approximately 5.3% of pregnancies. Several risk factors contribute to preeclampsia, including a history of preeclampsia, diabetes, chronic hypertension, kidney disorders, a family history of severe preeclampsia, obesity, maternal age, nulliparity, and multiple pregnancies. Medical records from Dr. R. Sosodoro Djatikoesoemo Bojonegoro Regency Hospital show that preeclampsia cases constituted 17.57% (195 of 1,110 cases) in 2020 and 8.26% (139 of 1,696 cases) in 2021. This study aims to analyze the risk factors for preeclampsia at RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro Regency. Methods: This observational analytic study employed a cross-sectional design. The sample consisted of 105 pregnant women in their second and third trimesters, selected using simple random sampling. Data were analyzed using the Multiple Logistic Regression Test to assess risk factors. Results: The multivariate analysis yielded a significance value of 0.243, indicating that maternal age, history of preeclampsia, and pregnancy spacing influence preeclampsia incidence. The Model Summary table showed Nagelkerke's R Square value of 0.037. Conclusion: Maternal age, pregnancy spacing, and a history of preeclampsia are significant risk factors for preeclampsia.